Analysis of Agrotourism Livelihood Assets in Batu City - Parlindungan, Soaniton David Stefanus; Riana, Fitria Dina; Andriani, Dwi Retno (Jurnal Social Economic of Agriculture, 2024)
With the increasing number of tourists visiting Batu City. This continuous increase represents an opportunity for the people of Batu City to develop their tourism sector. Agrotourism is one of the widely implemented tourism concepts in Batu City. Agrotourism is a concept that utilizes agriculture as its main attraction, aiming to provide recreational and educational experiences for tourists. This study aims to assess the development of tourism activities in Agrotourism in Batu City based on livelihood assets. The research utilizes a quantitative method employing the Asset Pentagon diagram. The analysis involves Livelihood Vulnerability Index (LVI) the assets to determine the most vulnerable one, visualized through a pentagon radar diagram. The measurement of livelihood assets includes variables such as human capital, social capital, natural capital, financial capital, and institutional capital. According to the results, the LVI in Desa Wisata Sidomulyo is 0.359, classified as "moderate" vulnerability the LVI in Desa Wisata Pandanrejo is 0.391, classified as "moderate" vulnerability the LVI in Wisata Eduaksi Dadaprejo is 0.266, classified as "low" vulnerability.